Into the gauntlet - Haddix, Margaret Peterson (New York : Scholastic, 2010)
Amy and Dan Cahill face their greatest challenge on their quest to find the thirty-nine clues, but in order to discover the secrets of their lineage they will have to make a choice that could impact the world's future.
May include trading cards.
Wilson's Children, September 2011.
Wilson's Junior High School, September 2011.
Horn Book, May 2011.
Wilson's Children.
Wilson's Junior High School.
Keywords: Families -- History -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Families -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Ciphers -- Fiction; Family secrets -- Fiction; Mystery and detective stories; Adventure and adventurers -- Fiction; Mystery fiction